Calcific tendonitis of the flexor pollicis longus tendon at the thumb interphalangeal joint in childhood. Issue 2 (4th March 2021) - Phan, Mimi; Birkemeier, Krista; George, Reshma; Garza-Gongora, Ricardo; Crisp, Matthew; Trotter, Bradley; Haghshenas, Varan
Abstract: In rare instances, calcific tendonitis may manifest in the pediatric population as inflammatory calcium hydroxyapatite deposition. To our knowledge, there have been no previous case reports involving the flexor pollicis longus tendon at the thumb interphalangeal joint. We present a 9-year-old boy with a painful mass at the right thumb interphalangeal joint. Initial radiographs revealed a 7-mm ovoid calcific mass along the volar soft tissues of the thumb interphalangeal joint. Subsequent ultrasound and magnetic resonance findings further confirmed calcification with surrounding edema. Because the pain was limiting the patient's school activities, his family elected for excisional biopsy of the calcific mass. Pathology ultimately revealed prominent dystrophic calcifications with surrounding granulomatous inflammation, consistent with calcific tendonitis.